Epidemiologic and Clinical Characteristics of Patients Presenting with Renal Colic in Korea - Hong, Dae Young; Kim, Jong Won; Lee, Kyeong Ryong; Park, Sang O; Baek, Kwang Je (Urology Journal, 2015)
Purpose: To investigate the epidemiologic and clinical characteristics of renal colic in Korea. Materials and Methods: Forty-six participating emergency departments provide their essential information to the National Emergency Medical Center. We extracted the National Emergency Department Information System data from January to December 2010. We analyzed data on demographics, visit time, chief complaints, mode of arrival, outcome, and length of stay. A total of 23,653 patients with renal colic visited the 46 emergency departments, and this patient population comprised 1.8% of all emergency department visits. Results: The median patient age was 45 years, and the male-to-female ratio was 2:1. The peak time of incidence for patients with renal colic occurred between 06:00 and 10:00 h. The peak incidence occurred in August, whereas the lowest incidence occurred in winter. The most common chief complaint was flank pain, followed by abdominal pain and hematuria. The median length of stay in the emergency department was 171 min, and female patients stayed longer in the emergency department relative to male patients. The median length of stay was shorter for weekend visits than for weekday visits. Most patients were discharged from the emergency department; only 6% of patients were admitted. Monday was the day with the highest admission rate. The length of stay did not correlate with age, whereas the admission rate increased with age. Conclusion: The epidemiologic and clinical features derived from this study may facilitate further investigations aimed at understanding the etiology of renal colic.